Book Review: The Judicial Process: Realism, Pragmatism, Practical Reasoning and Principles - Marten, Bevan (Victoria University of Wellington Law Review, 2006)
This article is a book review of E W Thomas The Judicial Process (Cambridge University Press, Cambridge, 2005) (414 + xxvi pages) Hardback NZ$180. In his belief that too many judges are simply 'muddling along' without a sound conception of what their role entails, Justice Thomas (a retired judge) has written a book putting forward a theory of judicial decision-making. The book represents the development of Thomas' thinking since an earlier monograph on the subject, but the two pillars on which he bases his theory remain unchanged: that the demands of justice in the individual case, and the requirement that the law meets society's reasonable needs, be at the forefront of every judgment. Marten notes that the book is deliberately pitched at a level that many people can read and enjoy. On the whole, Marten states that the book is a well-written and engaging book by one of New Zealand's most distinctive judges.